Reality monitoring measurement using Balls Control Test (BCT) Software. - Carlos Martínez-Suárez, Pedro; Andrés Buestán-Andrade, Pablo; Alexis Ramírez-Coronel, Andrés; Bernardo Cabrera-Mejía, Javier; Torracchi-Carrasco, Esteban; Gabriela Carpio-Carpio, María (Archivos Venezolanos de Farmacología y Terapéutica, 2021)
The monitoring of reality is a cognitive function involved in the discrimination of the stimulating source (internal or external). To measure this process, verbal paradigm tasks are used without considering that recent neuroimaging discoveries give a central role in source discrimination by stimulating basal ganglia and prefrontal motor cortex. For this purpose, a game was devised using a system of objects of different shapes whose number is variable in addition to their speed and size, with the particularity that the subject can control only one of them, and the rest are under the control of the program. Thus, the subject must find out which figure is under his control employing the directionals. The methodology used is based on the paradigm of object-oriented programming; each geometric figure is created through the concept of class so that properties such as shape, figure, dimensions, and behavior of objects are unique to each one. The main contribution is to have a precise non-verbal measure of the monitoring of reality, the time of discrimination of the source stimulated, as well as the errors made in the task and thus, matching these variables with other intervening variables to have a better knowledge of the nature of the process, to determine the role of motor feedback and in future research to have a cognitive marker that can be tested as an early predictor of schizophrenic spectrum disorders. These aspects are discussed at the end of the article.